The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1037/edu0000344
|View full text |Cite
|
Sign up to set email alerts
|

Do academics’ emotions in teaching affect their organizational commitment?

Abstract: This research pioneered the investigation of the statistically predictive power of academics' emotions in teaching for their organizational commitment-beyond age, academic rank, academic degree, sex, and taught academic discipline. Two hundred 22 academics from 13 higher educational institutions in Shanghai, mainland China, responded to a revised version of the Emotions in Teaching Inventory (Trigwell, 2009) and the Organizational Commitment Inventory (Ling, Fang, & Zhang, 2002). Results revealed that positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 63 publications
0
9
1
Order By: Relevance
“…Ling et al ( 2002 ) constructed the 20-item Organizational Commitment Inventory (OCI) to evaluate the five components (i.e., AC, NC, IC, EC, and CC) of organizational commitment among employees in industries in mainland China. Subsequent studies among academics (Zhang, 2015 , 2019 ; Zhang & Jing, 2016 ) consistently found that satisfactory psychometric properties of the OCI were more easily obtained with three items removed. Thus, the 17-item inventory was adopted in this study.…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations
“…Ling et al ( 2002 ) constructed the 20-item Organizational Commitment Inventory (OCI) to evaluate the five components (i.e., AC, NC, IC, EC, and CC) of organizational commitment among employees in industries in mainland China. Subsequent studies among academics (Zhang, 2015 , 2019 ; Zhang & Jing, 2016 ) consistently found that satisfactory psychometric properties of the OCI were more easily obtained with three items removed. Thus, the 17-item inventory was adopted in this study.…”
Section: Methodsmentioning
confidence: 96%
“…Generally, older academics report significantly more adaptive organizational commitment. Specifically, older academics reported higher levels of IC (Zhang, 2019 ), NC (Zhang et al, 2017 ) and AC (Zhang & Jing, 2016 ) than did younger academics. Two studies revealed that compared with academics in non-STEM disciplines, those in STEM disciplines expressed stronger AC and IC (Zhang, 2015 ; Zhang et al, 2017 ).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, the best teaching can be found in the attitude of the teachers, in their faith in their students' abilities to achieve, in their willingness to take their students seriously and to let them assume control of their own, learning and in their commitment to let all policies and practices flow from central learning objectives and from mutual respect and agreement between them and the students (Bain, 2011, p. 78-79). On a broader impact, Zhang (2019) found a strong association between teachers' emotions in teaching and their organizational commitment within the higher education context. Teachers with positive emotions in teaching are linked to adaptive forms of organizational commitment while maladaptive forms are associated with negative emotions in teaching.…”
Section: -Reflection Of University Teachers' Characteristicsmentioning
confidence: 97%